IMPLEMENTASI PERATURAN BUPATI BLORA NOMOR 45 TAHUN 2016 TENTANG KODE ETIK PEGAWAI NEGERI SIPIL DI SMP NEGERI 1 DOPLANG BLORA TAHUN 2021 - Asih Sulistyowati (Master of Public Administration, Universitas Slamet Riyadi, 2022)
SMP Negeri 1 Doplang, Blora a school with various kinds of characteristics of teachers and employees in it. The research is done by using the methods ofresearch descriptive qualitative, with technique collection of data that isobservation, interview and documentation. The data obtained were then analyzedinto a conclusion from the research process using the theory of Public PolicyImplementation according to George C. Edwards III. From research obtained theresults that indicators of communication has been implemented with effective.Indicators of resource human, there are less effective due to the limited ability ofthe competence and the factors of age, while the budget that is available on theagency that is already sufficient, disposition policies has been run by bothimplementing the policy already implementing the commitmen of each, as well asindicators of system bureaucracy implemented effectively. Keywords: Communication, Resources, Disposition, and Bureaucratic Structures